V 6 chasov vechera posle voiny - Pyriev, Ivan (Soviet Union : Mosfilm, 1944)
Designed as a successor to "They Met In Moscow", with the same director, star and composer, "Six PM." (1946 American release title) has two artillery officers meeting an attractive girl in Moscow between battles. One falls in love with her and they vow to meet in Moscow on a bridge at six pm when the war ends. The war puts them on diverse trails, but the pledge is fulfilled against the setting of Moscow's famous fireworks display.
Duration: 01:28:00
Keywords: Fiction films